The Tax Morality on Tax Compliance: Government Image as The Moderator Variable - Erdini Nugrahini; Ludigdo, Unti; Rahman, Aulia Fuad (Universitas Muhammadiyah Malang, 2026)
Purpose: This study aims to investigate the influence of government image as a moderating variable on the relationship between tax morale towards tax compliance Methodology/approach: This study used a descriptive survey method on Small Medium Enterprises (SMEs) in East Java Province, Indonesia, which was distributed online. This research employed PLS-SEM to analyse data from 126 SMEs. Findings: The findings of this study revealed that the government's image strengthens the influence of tax morale on tax compliance and the tax morale have a significant positive relationship with tax compliance Practical implications: This study presents practical implications for the government to improve the government's image by improving the quality of public services, transparency in tax administration, integrity of tax officials, and effective and accountable public communication. Originality/value: The novelty of this study lies in the use of government image as a moderating variable, referring to attribution theory and social exchange theory as an explanation for the newest phenomenon.